Oxford International Primary English: Workbook Level 1 - Yeomans, Anna; Miles Liz (Karachi Oxford University Press, 2022)
A comprehensive blended print and digital English programme for Years 1 to 6, Oxford International Primary English offers a clear and coherent literacy and language course with inspiring and culturally diverse content that puts each child at the heart of the learning experience. For Primary Literacy teachers in International schools following the Cambridge, ENC or OIC curriculum, this course is underpinned by a strong digital offer. Oxford International Primary English Offers a flexible, forward-looking and engaging route through primary English based on international best practice, with coverage of a range of curricula and a strong focus on wellbeing to fully prepare children for their onward studies.